토양 pH와 온도 조건이 농업용 항생제 옥솔린산의 생물학적 분해에 미치는 영향 - 김선희; Seon Hui Kim; 김가은; Ga Eun Kim; 조은혜; Eun Hea Jho (Hanguk hwangyeong nonghak hoeji, 2023)
Biodegradation of antibiotics in soil can be affected by various environmental factors. This study was set to investigate the effect of environmental conditions such as soil pH and temperature on the degradation of oxolinic acid (OA), one of the agricultural antibiotics used in South Korea, in soil. Rice paddy soil (RS) and field soil (FS) were contaminated with OA and the soil pH was adjusted to 5.7±0.2, 6.8±0.2, and 7.6±0.1. The soil samples were kept at different temperatures (2.3±0.2, 23.0±0.6, 30.5±0.3℃) for 30 d. The changes in the OA concentrations were determined at selected times. With the RS and FS, the OA removal was not affected by the soil pH used in this study; however, at pH 7.6, the OA removal in the RS was greater than that in the FS, which can be attributed to the different soil properties. The OA removal was similar at 23.0 and 30.5℃ in both soils, but was lower at 2.3℃. The information on the effect of different environmental conditions on the degradation of antibiotics in soil is very limited. Therefore, further studies are needed to better manage the residual antibiotics in the agricultural environment.